THE POST-WAR PERIOD IN THE ESTABLISHMENT OF OLEKSA IZARSKYI’S LITERARY INDIVIDUALITY - Руднянин, О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The paper studies the literary processes of the Ukrainian diaspora after the Second World War, analyzes the activitiesof the scientific migration centers.Special attention pays to the post-war period and its influence on OleksaIzarskyi’s individuality becoming as a writer.